Reversed-Phase HPLC Characterization and Quantification and Antioxidant Capacity of the Phenolic Acids and Flavonoids Extracted From Eight Varieties of Sorghum Grown in Austria - Speranza, Sofia; Knechtl, Rebecca; Witlaczil, Ragnar; Schönlechner, Regine (Frontiers in Plant Science, 2021)
Sorghum is raising great interest as a grain for the future, for its agricultural advantages in times of climate change, and for the positive impact of its bioactive compounds on human health. These compounds comprise phenolic acids, in a free, conjugated, and bound form, and flavonoids. The most commonly used extraction methods require high volumes of chemicals and are non-practical when handling many samples at a time. The main aim of this study was to develop a microscale extraction procedure for both phenolic acids and flavonoids to improve yield and diversity, labor time, and chemicals usage. The improved protocols allowed to perform the extraction in 2-ml safe-lock tubes using around 60 times less chemical volume for phenolic acids and 6 times less for flavonoids. In addition, compared to the macroscale method, the microscale approach was effective in extracting a comparable amount of phenolic acids (between 0.99 and 1.57 mg ferulic acid/g) and even a higher quantity of flavonoids (between 1.10 and 2.24 mg ferulic acid/g). With the established methods, phenolic compounds were extracted from eight varieties of sorghum grown in Austria, previously shown to be promising for food processing. In all sorghum varieties, protocatechuic, vanillic, caffeic, syringic, P-coumaric, and ferulic acids were detected in free, conjugated and bound form, with the last being the most abundant. Arsky and Icebergg varieties presented the lowest (922.65 μg/g) and the highest (1,269.28 μg/g) levels of total phenolic acids, respectively, recorded using high-performance liquid chromatography (HPLC). Flavonoids, comprising luteolinidin, apigenidin, naringenin, apigenin, 5-methoxy-luteolinidin (5-MetO-Lut), and 7-methoxy-apigeninidin (7-MetO-Api), were detected in amounts between 27.03 (Kalatur variety) and 87.52 μg/g (Huggo variety). The red varieties, Huggo, Armorik, and Arsky, had the highest antioxidant activity measured as 2,2-Diphenyl-1-picrylhydrazyl (DPPH) [around 5.00 μg Trolox equivalent (TE)/g] and Azino-bis(3-ehtylbenzthiazoline-6-sulfonic acid) (ABTS) (around 3.00 μg TE/g) scavenging capacity for both phenolic acids and flavonoids. Ferric reducing antioxidant power (FRAP) was the highest for the phenolic acids extracted from a white Ggolden variety.